Virtual Class During COVID 19: A Self-Regulated Learning Study Of Mathematics Pre-Service Teacher - Mohamad Gilar Jatisunda; Dede Salim Nahdi; Vici Suciawati (Universitas Ahmad Dahlan, 2020)
The massive spread of COVID 19 has disrupted the entire system of human life, including the education system. The policy decided by the Indonesian government regarding the learning process must be based online and the university's quick response by taking the initiative to use virtual classroom-based learning. However, with virtual classroom-based learning, independence is the main keyword for the success of student learning processes. The implementation of the virtual classroom-based learning process is based on constructivism theory. Student's initial knowledge becomes important in constructivist classes in achieving learning goals. This research is pre-experimental research with one shoot case study design. Determination of the research sample by purposive sampling technique with a sample size of 33 students of mathematics teacher candidates at Majalengka University. The statistical analysis used was Anova one path. The results showed that the scale of self-regulated learning for mathematics teacher candidates differed significantly based on initial knowledge categories (high, medium, and low). This study concludes that initial knowledge is an important part of student success in virtual classroom-based learning.